THE CONTRIBUTION OF CERTIFIED FRAUD EXAMINER (CFE) IN RISK MANAGEMENT OF THE BANKING INDUSTRY IN INDONESIA - Sofa Nur Ihtiari Wahyudi, Sofa Nur Ihtiari Wahyudi; Laila Sugiarta; Purnamasari, Pupung (UPT Publikasi Ilmiah UNISBA, 2024)
This research discusses the role of the Certified Fraud Examiner (CFE) in banking risk management in Indonesia. Using the literature study method, data regarding the adoption of contributions in preventing and detecting fraud were collected. The analysis results show that CFE has an important role in enterprise risk management, especially in fraud detection and fraud prevention. The Hexagon Fraud Theory, which elaborates on six factors that drive people to commit fraud, is analyzed in depth by considering the risk aspects that exist in the banking industry. This research proposes increasing the involvement of CFE-certified professionals in banking teams, as well as the need for collaborative research to evaluate the impact of CFE certification in more depth. It is recommended that banking companies continue to improve compliance with rules and regulations and build a corporate culture that supports effective risk management. Keywords : Banking Industry, Certified Fraud Examiner, Fraud Prevention, Hexagon Fraud, Risk Management.